2010
DOI: 10.5301/jbm.2010.6119
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of a Single Nucleotide Polymorphism of Insulin-Like Growth Factor-1 in Colorectal Cancer Patients and Its Association with Mucinous Adenocarcinoma

Abstract: Older patients had a higher frequency of the AA genotype of IGF-1(-2995 C/A), while younger patients more often had advanced disease and mucinous adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Caloric restriction was found to reduce cancer incidence in rodents and colorectal cell proliferation in humans [ 20 ]. The potential mechanism could be through insulin growth factor-1 (IGF-1), where increasing energy could be responsible for glycemic overload and a compensatory increase of serum insulin and related IGF-1, a promoter of tumor cell growth in vitro [ 21 , 22 ]. Elevated circulating insulin and IGF level may increase CRC risk, possibly by decreasing IGF-binding proteins (IGFBP-1) and increasing the bioactivity of IGF-I [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caloric restriction was found to reduce cancer incidence in rodents and colorectal cell proliferation in humans [ 20 ]. The potential mechanism could be through insulin growth factor-1 (IGF-1), where increasing energy could be responsible for glycemic overload and a compensatory increase of serum insulin and related IGF-1, a promoter of tumor cell growth in vitro [ 21 , 22 ]. Elevated circulating insulin and IGF level may increase CRC risk, possibly by decreasing IGF-binding proteins (IGFBP-1) and increasing the bioactivity of IGF-I [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Energy intake can be responsible for glycemic overload and a compensatory increase of serum insulin and related insulin growth factor-1 (IGF-1). IGF-1 is a promoter of tumor cell growth in vitro [43,44], and it may expose colonic and rectal cells to a proliferative stimulus [45,46]. Diabetes has also been related to increased CRC risk [47-49].…”
Section: Discussionmentioning
confidence: 99%
“…SNPs were genotyped according to a previous report . Genomic DNA was extracted from normal mucosa adjacent to the tumors in the surgical samples, and genotypes were determined by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, genome‐wide association studies (GWAS) have provided an opportunity to evaluate the genotyping of hundreds of thousands of single nucleotide polymorphisms (SNPs) in the genome and have been used to identify multiple genetic loci associated with increased or decreased CRC risk . By evaluating the independent effects of common SNP variants on CRC risk, several studies have found associations between CRC susceptibility loci and other parameters such as gender, tumor site, tumor stage, family history, and morphology . These associations provide additional evidence for the presence of different carcinogenic pathways across CRC subgroups.…”
Section: Introductionmentioning
confidence: 99%